2015
DOI: 10.4155/fmc.15.136
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments and Applications of Clickable Photoprobes in Medicinal Chemistry and Chemical Biology

Abstract: Photoaffinity labeling is a well-known biochemical technique that has grown significantly since the turn of the century, principally due to its combination with bioorthogonal/click chemistry reactions. This review highlights new developments and applications of clickable photoprobes in medicinal chemistry and chemical biology. In particular, recent examples of clickable photoprobes for target identification, activity- or affinity-based protein profiling (ABPP or AfBPP), characterization of sterol- or lipid-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 85 publications
0
46
0
2
Order By: Relevance
“…This benzophenone can be prepared with multiple functional groups at the para position of the other phenyl ring (CH 2 Br, CHO, CH 2 OH, CO 2 H, CH 2 NH 2 ), which constitute versatile intermediates for synthesis of clickable photoaffinity probes. 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This benzophenone can be prepared with multiple functional groups at the para position of the other phenyl ring (CH 2 Br, CHO, CH 2 OH, CO 2 H, CH 2 NH 2 ), which constitute versatile intermediates for synthesis of clickable photoaffinity probes. 1 …”
Section: Discussionmentioning
confidence: 99%
“…In some cases, a diazirine- or aryl azide-based photoreactive probe is advantageous, while in other cases a benzophenone-based probe is preferred. 1,2,1825 Benzophenone-based probes are commonly utilized for identification and characterization of γ -secretase, 46,2631 a macromolecular complex linked with Alzheimer’s disease (AD). 32,33 Fuwa et al 34 compared different photoreactive groups and showed that only benzophenone containing γ -secretase inhibitor probes cross-linked to presenilin (PS), the catalytic subunit of γ -secretase, 35 or SPP, but not phenyl-diazirine probes, despite similar inhibitory potencies.…”
mentioning
confidence: 99%
“…Dazu werden zellpermeable,n iedermolekulare Sonden verwendet, die einerseits eine Gruppe zur kovalenten Bindung an das Protein enthalten und außerdem über eine Funktionalität, z. [124][125][126] Ein anschauliches,j üngstes Beispiel ist die Aufklärung des Zielproteins des Pseudomonad-Sekundärmetaboliten Promysalin. Im Anschluss an die Bindung der zellulären Zielproteine und die Zelllyse kann die Alkin-Einheit zur Konjugation an Azid-modifizierte Fluorophore oder Affinitäts-Tags mittels Kupfer-katalysierter Klick-Reaktion verwendet werden.…”
Section: Identifizierung Und Validierung Der Biologischen Zielstrukturunclassified
“…Seeking to replace the acetyl lysine mimetic of the CREBBP probe SGC-CBP30, Jones and co-workers identified a novel photoreactive tropolone warhead, and hypothesized that photoaffinity labels could be developed for bromodomains. Shown to indeed be possible, a clickable derivative was accessed which was used to understand the direct biological targets of the probe and assess BRD4 target engagement by (+)-JQ-1 [15,16]. Clickable photoaffinity labeling probes have also been used to map thousands of site-specific small-molecule protein interactions within human cells, from which more potent and selective small molecules can be optimized, presenting this technique as a versatile approach to small-molecule discovery as we advance into the future [17].…”
Section: Small Molecules and Their Role In Effective Preclinical Targetmentioning
confidence: 99%